(untitled) (Journal of The Colloquium for Information Systems Security Education, 2020)
There is currently a shortage of cybersecurity professionals worldwide. This paper presents an after-school program for high school students to explore cybersecurity topics and careers. The paper discusses the content of the course as well as the results that have been seen to date. A link to an online repository of program materials will be shared with the audience. This work effort is the result of the NSF funded grant Improving the Pipeline: After-School Model for Preparing Information Assurance and Cyber Defense Professionals (Grant No. 1623525).